Answer:
which agrees with the answer D of your options
Step-by-step explanation:
Notice that the graph of G(x) has the initial graph shifted horizontally to the right in 6 units, therefore such horizontal shift is accomplished by subtracting the 6 units from the x-variable in the original expression:
It will be greater than the length of the third side always
Let's solve this by using the quadratic formula:
Note that we only use the coefficients so a=12, b=-14, and c=-6.
Plug values in the quadratic equation:
And so by evaluating those values we obtain:
Now we have two answers which are our factors one where we add another where we subtract and so:
First factor:
Second Factor:
And so your factors are
meaning that those are your roots/x-intercepts.
Answer:
I keep getting no solution
Step-by-step explanation:
Step 1: Simplify both sides of the equation.
5(x−4)=−9+5x+15
(5)(x)+(5)(−4)=−9+5x+15(Distribute)
5x+−20=−9+5x+15
5x−20=(5x)+(−9+15)(Combine Like Terms)
5x−20=5x+6
5x−20=5x+6
Step 2: Subtract 5x from both sides.
5x−20−5x=5x+6−5x
−20=6
Step 3: Add 20 to both sides.
−20+20=6+20
0=26
Answer: {x,y}={-1,2}
step-by-step explanation:
// Solve equation [2] for the variable x
[2] 2x = 5y - 12
[2] x = 5y/2 - 6
// Plug this in for variable x in equation [1]
[1] 2•(5y/2-6) + 3y = 4
[1] 8y = 16
// Solve equation [1] for the variable y
[1] 8y = 16
[1] y = 2
// By now we know this much :
x = 5y/2-6
y = 2
// Use the y value to solve for x
x = (5/2)(2)-6 = -1
Solution :
{x,y} = {-1,2}